Human Capital, Inequality, and Poverty: Pathways to Achieving SDGs 1 and 10 - Eza Nur Fauzan; Amir Machmud; Endang Supardi (Jurnal Ekonomi Pembangunan, 2026)
This study aims to analyze the relationship between human capital, income inequality, and poverty within the framework of achieving Sustainable Development Goals (SDGs) 1 and 10. The method used is bibliometrics by following the PRISMA guidelines. The results of the study show that human capital plays an important role in reducing poverty, especially through improving education, skills, and health. However, its effectiveness is greatly influenced by the distribution of opportunities and the level of income inequality. When access to human capital is unequal, its benefits tend to widen social disparities, so that poverty alleviation efforts be less than optimal. These findings underscore the importance of integrating human development policies with economic redistribution strategies to ensure that social investments are truly inclusive and equitable. The originality of this research lies in its comprehensive mapping of the latest literature linking the three main dimensions of human capital, income inequality, and poverty within the SDGs framework. The practical implication is that governments and policymakers need to ensure that investments in human capital are accompanied by equitable access, so that they can be an effective instrument for sustainable poverty reduction